Predictors of organizational commitment among university nursing faculty of Kathmandu valley, Nepal. - Timalsina, Rekha
ABSTRACT: Increasing work efficiency, improving psychological health, decreasing turnover, turnover intention and absenteeism may be dependent on organizational commitment of and employee. A cross- sectional analytical study was carried out for identifying the predictors of organizational commitment among 197 university nursing faculty of Kathmandu valley, Nepal. A proportion stratified random sampling technique was used for selecting samples from 18 colleges of nursing. Structured self-administered questionnaires were used for the collection of data. Double data entry and data cleaning was done using Epi-data software and data analysis was done using SPSS software version 16.Chi-square test was used for analyzing the association and regression analysis were used for identifying the predictors of organizational commitment. The findings of this study showed that married nursing faculty, nursing faculty having: favourable perception towards faculty developmental opportunity and high level of perceived organizational support had high level of affective commitment. Nursing faculty having permanent appointment had high level of affective, normative and organizational commitment than others. The nursing faculty who had completed master in nursing had position of assistant instructor to assistant lecturer level and work commitment. It is concluded that the predictors of: affective commitment are marital status, type of appointment, perceived faculty developmental opportunity, job satisfaction and perceived organizational support; normative commitment are type of appointment; and organizational commitment are academic qualification in nursing, position, type of appointment, current organizational tenure and job satisfaction. Therefore, organization must pay attention to these predictors for enhancing organizational commitment of nursing faculty. So that it may reduce turnover of them, improve work efficiency evidenced by quality of teaching and student's satisfaction. Keywords: organizational commitment, predictors, university nursing faculty.